Dye sensitised solar cells and time resolved photoacoustic calorimetry on thin films. - Johann Josef Anton Schabauer (2008)
This work is primarily a study of the photoelectrochemical characterisation of dye sensitised solar cells. The specific parts of the cell and their role towards overall cell efficiency are considered in detail. A large number of cells have been characterised in which the nature of: the TiO2 semiconductor, the absorbing dye, electrolyte, and the nature of the conducting electrodes, were varied. The photoelectric properties of the cells were measured using a Xe-arc sun simulator mimicking the incident solar radiation at ground level. Cell voltage and current were measured while operating under different temperatures and irradiation intensities. It was found, that a thick layer of Pt at the counter electrode did not improve the performance of the cell. Plastic cells are smaller and lighter, but lack in efficiency when compared to glass cells which is down to the lower series resistance of the transparent conducting oxide used. Higher concentrated electrolytes can lead to better results. At higher illumination intensities, back irradiation of the cell becomes favourable down to charge transfer limitations, especially in gel and solid electrolytes. Another significant part of the research documented in this thesis was the development of thin film and interfacial time resolved photoacoustic calorimetry as a novel method for the time resolved measurement of non-radiative processes of dyes adsorbed at interfaces or as thin solid films. In our case, the dyes were either adsorbed on the mesoporous TiO2 semiconductor film used in dye sensitised solar cells, or incorporated in a polymer matrix. Using this approach, we were able to directly measure triplet state lifetimes and quantum yields of charge injection into the semiconductor. Possible further applications for this method are discussed.